PENDIDIKAN ĀTMAVIDYĀ SEBAGAI METODE PENGENDALIAN DIRI DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - I Made Dwi Susila Adnyana Dwik (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The Industrial Revolution 4.0 is a revolutionary industrial transformation model based on the connectivity of cyber systems in its implementation. The rapid change of world civilization in various countries is marked by the use of limitless information systems based on computing and big data. The positive impacts that can be felt are the ease of accessing information using gadgets, the ease of learning using e-learning, and so on. However, on the other hand, the Industrial Revolution 4.0 also has negative impacts such as being more vulnerable to cyber-attacks and easy access to illegal sites, making it very risky for the degradation of human morality. To anticipate and minimize these matters, a special method is needed that aims to control oneself. If in human beings it can be controlled and controlled in accordance with the rules of truth (dharma), then the output produced will also be in accordance with the true essence of